The Ilizarov Technique: A Dynamic Solution for Orthopaedic Challenges - Shengsheng Guan; Hui Du; Yong Wu; Sihe Qin (Orthopaedic Surgery)
The Ilizarov technique is one of the most important tools that is currently employed in bone reconstruction surgeries. Its inception dates back to the mid‐20th century and involves various bone reconstruction methodologies implemented using a circular external fixator system devised by G. A. Ilizarov. The key advantages of this approach include the generation of viable new bone via distraction osteogenesis, high union rates, and the functional utilization of the limb during the treatment process. The exploration of distraction osteogenesis phenomenon triggered by tensile stress with the Ilizarov device served as a catalyst for progress in bone reconstruction surgery. Subsequently, the original technique has been utilized alongside several adaptations resulting from the introduction of novel fixation tools and methods of their application, such as hexapod external fixators and motorized intramedullary lengthening nails. It is crucial to possess a precise comprehension of the Ilizarov principles of deformity correction in order to effectively utilize this fixation system. In this article, we will discuss the history of Ilizarov frame, the basic sciences behind it, the mechanical principles governing its use, and the clinical application of the fixation system in our daily practice.